The Prospects for Public Management Reform in Indonesia - Muhtada, Dani (Faculty of Law, Universitas Negeri Semarang, 2017)
After the fall of Suharto, the government of Indonesia has started to reform its public sector. The reform began with the introduction of Law 22/1999 on Regional Autonomy and Law 25/1999 on Fiscal Equalization between Center and Regions. The laws have created a huge wave of decentralization in almost all aspects of the management of Indonesia’s public sector. Yet, the future of such a reform is debatable. This article discusses the prospects for public management reforms in Indonesia. This author argues that the government needs clear rules for effective implementation of decentralization. The government also needs to reinforce the role of provincial governments as the agents of the central as well as the coordinator of district governments. Furthermore, the government needs to set standard budgeting, auditing, and reporting procedures for all local budgets, and mechanisms in order to monitor sharing of natural resources revenue and transfers. Last but not least, the role of non-government organizations (NGOs) and mass media is highly significant and required for a successful reform of public management.